Perfluoroalkyl substances in Arctic birds : a comparison between glaucous gulls and black guillemots from Svalbard - Axelson, Siri (SLU/Dept. of Aquatic Sciences and Assessment, 2014)
Perfluoroalkyl substances (PFASs) are ubiquitous in the environment today and they have been detected even in remote areas such as the Arctic. PFASs can be transported by the atmosphere and ocean currents but the transport mechanism is not fully understood. PFASs may be harmful to organisms due to their persistence in the environment, bio-accumulation potential and toxicity. Studies have shown that PFASs can cause adverse effects on the metabolism as well as the endocrine- and reproduction systems in organisms. In this study, PFASs were investigated in glaucous gull (Larus hyperboreus) (n=5) and black guillemot (Cepphus grylle) (n=4) from Svalbard. In glaucous gull, the mean ∑PFAS concentrations were 147 ng g-1 in liver and 15 ng g-1 in muscle. In black guillemot, the mean ∑PFAS concentrations were 36 ng g-1 in liver and 2.5 ng g-1 in muscle. Perfluorooctane sulfonate (PFOS) was the most abundant compound, constituting in average 72 % of the ∑PFASs. The mean PFOS concentration was more than four times higher in glaucous gull than in black guillemot. This can be explained by the glaucous gull’s high trophic level, migration patterns to more industrialized areas, and omnivorous feeding patterns. The concentration levels were higher in liver than in muscle tissue for both species, which complies with other similar studies. This might be due to the fact that PFAS typically accumulate in protein-rich tissues with high blood content, and that the liver has a detoxifying function and takes care of the contaminants in the body. As PFASs are produced in industrial areas far away from Svalbard, the detected concentration levels in the studied species give reason to further investigate the fate and transport of PFASs, as well as their effects on wildlife in the Arctic region. Perfluouroalkylerade ämnen (PFASs) är en grupp föreningar varav många är allmänt förekommande i miljön idag. Dessa ämnen har upptäckts även i avlägsna områden såsom Arktis. Mekanismerna för transporten av PFASs till Arktis är inte helt fastställda, ...